Analyse Économique Du Secteur Industriel Au Maroc - El Ouahabi Sanae; Bousselhami Ahmed (European Scientific Journal, ESJ, 2018)
In this study, we will focus on the different dimensions of performance, and make a descriptive analysis of the industrial sector’s position in the national economy. We will also assess the clout and the performance of each industrial branch, through the measurement of the following indicators: the added value, the employment, the number of companies, the investment, the foreign trade, the comparative advantage and the degree of export commitment. This research shows that the industry contributes the most to GDP with an average of about 19% during the 1985-2016 period, followed by agriculture with (15%), trade with (12%), construction industry and public works with (5%). By industry, statistics show the predominance of the agri-food, textile, leather, mechanical, metal and electrical industries in overall industrial production over the period 1985-2016, while in terms of exports, the mechanical, metallic, electrical", and "textile and leather" branches are at the top of the list with a share of 27% for each. Over the period of 1985-2014, the chemical and parachemical industry ranks first in terms of investments in the industrial sector with a 33% share, and thus promises significant growth prospects. In terms of regions, figures show the predominance of the Grand Casablanca region, which accounts for 41% of companies created, 61% of national industrial production, 56% of industrial exports, and 50% of the total workforce employed during the 1985-2014 period. All this is happening with a remarkable rise of the Tangier-Tetouan region in recent years.